2019
DOI: 10.1007/s11705-018-1786-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma for cancer treatment: How can RONS penetrate through the cell membrane? Answers from computer modeling

Abstract: Plasma is gaining increasing interest for cancer treatment, but the underlying mechanisms are not yet fully understood. Using computer simulations at the molecular level, we try to gain better insight in how plasma-generated reactive oxygen and nitrogen species (RONS) can penetrate through the cell membrane. Specifically, we compare the permeability of various (hydrophilic and hydrophobic) RONS across both oxidized and non-oxidized cell membranes. We also study pore formation, and how it is hampered by higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…In contrast, when lower concentrations of cholesterol were present (i.e., cancer cells), the cell membrane was more vulnerable to oxidative stress and it favoured pore formation [48]. The pores generated in the cell membrane facilitated the pass of plasma-generated ROS into the intracellular compartment [67,68], where they could exert further oxidative damage to cells. Our simulation results are in agreement with the literature, as we demonstrate here that RONS present in PT-PBS (e.g., H 2 O 2 , NO 3 − and NO 2 − ions [24,30] oxidize the cell membrane (as can be deduced from the lipid peroxidation experiments, see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when lower concentrations of cholesterol were present (i.e., cancer cells), the cell membrane was more vulnerable to oxidative stress and it favoured pore formation [48]. The pores generated in the cell membrane facilitated the pass of plasma-generated ROS into the intracellular compartment [67,68], where they could exert further oxidative damage to cells. Our simulation results are in agreement with the literature, as we demonstrate here that RONS present in PT-PBS (e.g., H 2 O 2 , NO 3 − and NO 2 − ions [24,30] oxidize the cell membrane (as can be deduced from the lipid peroxidation experiments, see Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, nanotechnology combined with CAP technology has exhibited some promising aspects in cancer research by the activation/deactivation of cellular pathways [17]. Additionally, it has been proposed by some research groups that CAP can help in selective cell membrane permeability, which helps in the invasion of CAP-generated direct and indirect RONS species, leading to the intracellular invasion of nanoparticles towards applied sites [18][19][20]. However, at the clinical level, the outcome of the survival of melanoma patients has been very limited due to the targeted mutation in molecular targeted therapy [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because a common treatment of OS is a surgical resection of the tumor, direct treatment can also be applied to treat resection margins to eliminate remaining tumor tissue and allow for more conservative surgery ( Figure 3 A) [ 54 ]. The exposure to electromagnetic fields in direct treatment may lead to an increase in cell permeability or cell membrane disruption, which can improve the in situ uptake of RONS [ 95 , 96 ] and drugs [ 73 , 97 , 98 ]. Moreover, it has been suggested that the destruction of the tumor extracellular matrix (ECM) may improve the response of tumors to chemotherapy or other treatments [ 99 ], reducing the effective doses needed for postoperative regimens.…”
Section: Potential Application Of Cap In Osmentioning
confidence: 99%